Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan Pada PT. Hanjaya Mandala Sampoerna Tbk. - Muhammad Ali Najib; Zaimah Zaimah; Ratih Kusumastuti (Populer: Jurnal Penelitian Mahasiswa, 2023)
This research aims to analyze the financial performance of PT. H.M Sampoerna Tbk based on financial ratio data from 2018 to 2022. The study adopts a quantitative approach using a descriptive study method by collecting and analyzing the company's financial data. Liquidity, solvency, and profitability ratios are utilized to measure the financial performance of the company. The findings indicate that there are variations in the company's financial performance during the research period. Nonetheless, the company still records adequate net profit and returns. However, it is crucial for the company to enhance liquidity management, carefully manage debt, and improve operational efficiency to achieve sustainable growth in the future.